2002
DOI: 10.1034/j.1399-3054.2002.1140302.x
|View full text |Cite
|
Sign up to set email alerts
|

The dose–response curve of the gravitropic reaction: a re‐analysis

Abstract: The dose-response curve of the gravitropic reaction is often used to evaluate the gravisensing of plant organs. It has been proposed (Larsen 1957) that the response (curvature) varies linearly as a function of the logarithm of the dose of gravistimulus. As this model fitted correctly most of the data obtained in the literature, the presentation time (tp, minimal duration of stimulation in the gravitational field to induce a response) or the presentation dose (dp, minimal quantity in g.s of stimulation to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 43 publications
1
60
0
Order By: Relevance
“…Investigations with excess starch mutants indicate that gravisensing is not saturated 41 and studies of the presentation time show that much shorter reorientation times than signal saturation are sufficient to induce curvature and suggest that amyloplast sedimentation is not necessary for the initiation of gravitropism. 40 While earlier studies focused on the detection limit (presentation time) that is sufficient to induce curvature, 28,35 this study demonstrates saturation of the gravity stimulus likely coincides with the amyloplast sedimentation. Studies on gravity-induced gene expression, hormone redistribution and signal transduction should use this time as reference point for maximal effects of a (single) acceleration or reorientation stimulus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Investigations with excess starch mutants indicate that gravisensing is not saturated 41 and studies of the presentation time show that much shorter reorientation times than signal saturation are sufficient to induce curvature and suggest that amyloplast sedimentation is not necessary for the initiation of gravitropism. 40 While earlier studies focused on the detection limit (presentation time) that is sufficient to induce curvature, 28,35 this study demonstrates saturation of the gravity stimulus likely coincides with the amyloplast sedimentation. Studies on gravity-induced gene expression, hormone redistribution and signal transduction should use this time as reference point for maximal effects of a (single) acceleration or reorientation stimulus.…”
Section: Discussionmentioning
confidence: 96%
“…28,29 Despite the usefulness of a clinostat as a gravity compensator, it introduces its own problems such as the destruction of columella cells in the root cap. 30,31 Clinostatinduced complications are likely to interfere with the original gravistimulus and sensed and probably processed as mechanostimulation that is superimposed to the gravity stimulus and response.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the early differences in tt4(2YY6) root gravity responses, gravity perception appears unhampered in this mutant. Examination of the presentation time and the gravity sensitivity, two estimates of the minimum time of gravity stimulation that will induce gravitropic bending, were obtained from two graphical methods (Larsen, 1957;Perbal et al, 2002). Both methods indicated that the tt4(2YY6) mutant is not impaired in gravity perception.…”
Section: Discussionmentioning
confidence: 99%
“…The clinostat randomizes the gravity vector by rotating the samples continuously at 1g, allowing additional gravity-independent elongation, to assess the response to the initial gravity stimulus. The angle of gravitropic curvature change was measured after clinorotation and plotted using the linear-log model (Larsen, 1957) and the hyperbolic method (Perbal et al, 2002) to estimate the minimum time likely to induce bending and determine gravisensitivity, respectively. These graphs are included as supplemental data online.…”
Section: Tt4(2yy6) Roots Exhibited a Delayed Gravity Response And Narmentioning
confidence: 99%
“…This constant 1g background poses significant challenges for defining the temporal sensitivity of the plant gravisensing machinery. In previous studies, the minimum duration of gravistimulation needed to induce a detectable response, "the presentation time" for gravitropic responses (Perbal and DrissEcole, 2003), has been estimated indirectly (Perbal et al, 2002) and is probably less than 10 s in Lepidium sativum roots (Hejnowicz et al, 1998).…”
Section: Relationship Between the Amplitude Of The Sustained [Ca 2+ ]mentioning
confidence: 99%